2016
DOI: 10.1890/14-2393
|View full text |Cite
|
Sign up to set email alerts
|

Pastoral and woodcutting activities drive Cedrus atlantica Mediterranean forest structure in the Moroccan Middle Atlas

Abstract: Human activities are historical ecological drivers, and we need to better understand their effects on ecosystems. In particular, they have been very important in the shaping of the Mediterranean biodiversity hotspot. Researchers and managers nonetheless lack knowledge concerning the impacts of their combinations and their current intensity on the structure of forest ecosystems of the southern part of the Mediterranean basin. In this study, we have develped a new methodology in order to understand the impacts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Regional field-data assessments (Coudel et al, 2016) and the use of modelling and remote sensing techniques (Bottalico et al, 2016(Bottalico et al, , 2017 can improve our understanding of long-term and broad-scale impacts of management practices on the structure and function of forest ecosystems.…”
Section: Improving the Scientific Basis Of Forest Adaptation Strategiesmentioning
confidence: 99%
“…Regional field-data assessments (Coudel et al, 2016) and the use of modelling and remote sensing techniques (Bottalico et al, 2016(Bottalico et al, , 2017 can improve our understanding of long-term and broad-scale impacts of management practices on the structure and function of forest ecosystems.…”
Section: Improving the Scientific Basis Of Forest Adaptation Strategiesmentioning
confidence: 99%
“…This development will likely hasten dominant species replacement in this region [16]. Recent studies have found an interaction gradient between pastoral and woodcutting activities, where the disturbance having the most impact on C. atlantica stand structure is grazing and pruning [29]. This study concludes that the structure differences depend more on human activities than on environmental parameters.…”
Section: Discussionmentioning
confidence: 63%
“…Its extant distribution is limited to mountainous regions of Morocco and Algeria where it is threatened by anthropogenic activities. Semi-nomadic pastoral tradition, widespread across the Rif and Atlas Mountains, continues to generate an intensive grazing pressure that severely prevents natural regeneration [26,32]. Recent increased aridity and temperature led to a decrease in growth rate and an increase in mortality [25,26,28,29].…”
Section: Introductionmentioning
confidence: 99%